Geotechnical aspects of the Kalayaan pumped storage project Philippines - Vargas, Emmanuel Arcilla; Akagi, T.; Nutulaya, P.; Balasubramaniam, A.S.; United States Agency for International Development (USAID) Red (Bangkok : Asian Institute of Technology, 1980)
The study covers some of the important geotechnical considerations related to the construction of the Kalayaan Pumped Storage Project in Laguna, Philippines. The specialized and complex construction techniques with special reference to the excavation of the powerhouse shaft and penstock tunnels are comprehensively described. The installation of plastic drain (Geodrain) to accelerate consolidation of the very compressible soil in the area and the construction of the diaphragm wall by the slurry trench technique are likewise described including the preliminary reclamation and preloading works. The coverage of instrumentation and the various instruments employ{u2014} ed for monitoring movement of foundation soil and structures are given full discussion. Additionally, two analyses are performed, settlement analysis of the reclaimed area in an attempt to define the average in{u2014}situ compressibility characteristics of two settlement sections, and the stability analysis of the natural slope at the upper canal, to evaluate the stability condition of the slope. Recognizing the inherent variability of a residual soil, the effect of a wrongly assumed soil parameter in the computed factor of safety is further analyzed. The two solutions (remedial measures) proposed for implementation to enhance the stability condition of the slope are also discussed.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1980
Keywords: Soil mechanics